PERBANDINGAN PENDEKATAN DAKWAH DAN ADAT ISTIADAT TERHADAP ADAT ISTIADAT LOKAL: STUDI LITERATUR TERHADAP DUA JURNAL ILMIAH - Hasanudin Al Ghifari; Abdul Mulqi; Sobirin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This literature study analyzes da’wah strategies in the context of cultural acculturation, based on two journals: “Javanese Cultural Acculturation as a Da’wah Strategy” and “Muhammadiyah’s Cultural Da’wah Strategy in the Mappogau Hanua Ritual of the Karampuang Community in Sinjai.” The first journal discusses the process of Javanese cultural transformation, which is divided into three historical phases: the pre-Hindu-Buddhist period, the Hindu-Buddhist period, and the arrival of Islam. During the Islamization phase, it is evident that da’wah was carried out through a local cultural approach. Cultural media such as arts, oral traditions, and customary symbols were utilized to convey Islamic teachings, resulting in a cultural synthesis rich in religious values while remaining rooted in local identity. Meanwhile, the second journal highlights the da’wah approach undertaken by Muhammadiyah in Karampuang, South Sulawesi. In this context, Muhammadiyah did not immediately reject the traditional Mappogau Hanua ritual but instead sought to understand it, then gradually reconstruct these practices to be more aligned with Islamic teachings. This strategy was accompanied by community empowerment through education, healthcare, and collaboration within the traditional governance structure. As a result, a gradual yet consistent change in the mindset and behavior of the community took place. Both studies emphasize the importance of cultural and contextual da’wah. Adjusting da’wah methods to local cultural characteristics has proven effective in fostering an inclusive, non-confrontational, and sustainable process of Islamization. The cultural differences between the Javanese and South Sulawesi communities further enrich our understanding of the diverse da’wah strategies that can be applied within Indonesia’s cultural plurality. Keywords: Da’wah Strategy, Cultural Acculturation, Javanese Culture, Islamization